2015
DOI: 10.12816/0011365
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and Pathological Findings in Partial Nephrectomy for Renal Masses : Experience at King Hussein Medical Center

Abstract: Objective:The aim of this study is to assess the accuracy of radiologic findings of renal masses by comparing them with the histopathologic diagnoses from our personal experience in partial nephrectomy specimens. Methods:We reviewed the histopathological reports of 49 patients who underwent partial nephrectomy in a 10 year duration at Prince Hussein bin Abdullah urology and organ transplant centre Results: Only 32 patients of 49 harbored renal cell carcinoma in their specimens with a percentage of 65.4%. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In contrast, Alkaabnah et al reported a higher benign rate of 30% in patients undergoing partial nephrectomy. 12 Nakashima et al attributed a low benign incidence rate of 6.63% in their study to the use of magnetic resonance imaging (MRI) in conjunction with CT scan in their patients, as MRI is known to be more sensitive in detecting small amounts of intralesional fat. 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Alkaabnah et al reported a higher benign rate of 30% in patients undergoing partial nephrectomy. 12 Nakashima et al attributed a low benign incidence rate of 6.63% in their study to the use of magnetic resonance imaging (MRI) in conjunction with CT scan in their patients, as MRI is known to be more sensitive in detecting small amounts of intralesional fat. 8…”
Section: Discussionmentioning
confidence: 99%
“…8,9,10,11,16 Ethnicity may predict the type of benign tumours found at nephrectomy performed for presumed RCC, with most Asian studies reporting angiomyolipoma as the most common benign tumour and studies from the US reporting oncocytoma. 2,8,10,11,12 Oncocytoma cannot be confidently distinguished from RCC on imaging. 11,16 We expected that given the high burden of infectious diseases in South Africa, we would see more inflammatory lesions such as xanthogranulomatous pyelonephritis, tuberculosis and aspergillosis being mistaken for RCC.…”
Section: Discussionmentioning
confidence: 99%